Intrinsic transition mechanism to detonation of gaseous laminar flames in tubes - Clavin, Paul (Comptes Rendus. Mécanique)
The deflagration-to-detonation transition (DDT) on the tip of an elongated flame in a tube is analyzed in the double limit of large activation energy and small Mach number of laminar flames. A spontaneous transition of a self-accelerated laminar flame taking the form of a dynamical saddle-node bifurcation of the flow inside the inner structure of the laminar flame is exhibited by the asymptotic analysis. The predicted critical conditions for the finite-time pressure runaway are in good agreement with the experimental data of the DDT onset in tubes.